Methods of State Regulation of Innovation in the Modern Economy of Russia - Ablaev, Ildar M. (Opción, 2019)
It is innovations that create a competitive advantage and provide economic growth. This article studies methods of regulating innovations in Russia. Comparative indicators of regulating innovations in Russia, the USA, Europe, China, and also Japan are given. To achieve this goal, statistical data were used, and Russian legislation in this area was also monitored. As a result, the characteristics of the methods for regulating Russia's innovations and its main differences from other countries are given. It is stated that the business climate needs to be improved in Russia, since at this stage mainly the state invests in the innovation sphere.